Harmony amidst dissonance: unveiling the power of open communication in resolving demarketing dilemmas - Fiona Kigen; Marike Venter de Villiers (Cogent Business & Management)
Cognitive dissonance (CD) is a well-established concept in marketing literature, particularly within consumer behavior contexts. This study extends its application to the underexplored domain of demarketing in the banking sector, specifically addressing the challenges banks face in managing loan rejections. Unlike traditional studies on post-purchase dissonance or general dissatisfaction, this research examines how deliberate, firm-initiated actions – such as demarketing – create CD while requiring strategies to retain customer loyalty. The study investigates the role of communication openness (CO) as a moderator in the relationship between CD, satisfaction and loyalty. By highlighting how open communication mitigates the adverse effects of demarketing decisions, the research provides a fresh perspective on preserving customer relationships in adverse scenarios. Methodologically, the study employs a vignette-based approach combined with structural equation modeling (SEM), analyzing 505 responses, offering a robust framework for understanding customer reactions. This methodological design allows for rigorous statistical validation of complex relationships. The findings contribute to the literature on demarketing and relationship marketing, offering actionable strategies for banks to navigate the delicate balance of rejecting customer requests while fostering long-term loyalty.